Assessment of soil redistribution on two contrasting hillslopes in Uganda using Caesium-137 modelling - Ruecker, Gerd R.; Park, Soojin J.; Brunner, Almut C.; Vlek, Paul L. G. (ERDKUNDE, 2008)
The assessment of soil erosion by Caesium-137 (137Cs) modelling has achieved widespread applications in many regions of the world. Especially for countries in the humid tropics experiencing severe soil degradation, this approach offers the potential to quickly quantify the spatial distribution of soil loss, in order to propose site-specific erosion control measures. This research aims to examine the potential for utilizing the 137Cs approach to assess soil redistribution rates in the humid tropics of Uganda. More specific research objectives are: 1) to investigate the 137Cs modelling approach and its potential for erosion and sedimentation assessments in the humid tropics of Africa; and 2) to identify the spatial distribution of erosion and sedimentation on two contrasting hillslopes in Uganda. Two cultivated hillslopes with contrasting agro-ecological conditions were selected: one highland site with unimodal rainfall distribution with mollic andosols and a relatively steep slope of up to 18% (Kongta), and one lowland site with bimodal rainfall distribution, strongly weathered plinthic ferralsols and a gentle slope of a maximum of 10% (Magada). 137Cs inventories from reference samples were collected in the vicinity of these sites and 137Cs inventories from samples were extracted from the intersections of a regular sampling grid that covered each hillslope. The average 137Cs reference inventories were 392 and 439 Bq m-2, for Kongta and Magada, respectively, which are within the range of the globally interpolated 137Cs inventory estimated for this region. The modeled net soil redistribution indicated for both sites soil erosion with higher soil losses in Kongta (-21 t ha-1 year-1) than in Magada (-4.5 t ha-1 year-1). Peak hillslope erosion rates were 44.6 t ha-1 year-1 in Kongta compared to 36.3 t ha-1 year-1 in Magada. In contrast, sedimentation rates in Magada were as high as 25 t ha-1 year-1 and significantly higher than in Kongta with 6.4 t ha-1 year-1. These 137Cs-based soil redistribution rates were similar to erosion assessments within the same ecological zone based on erosion plot studies and other model applications. Despite the low fallout and some other obstacles, we conclude that the 137Cs method might be a suitable alternative technique to estimate soil redistribution on hillslopes in the humid tropics of Africa, such as in the southern region of Uganda.